2020
DOI: 10.1080/21645515.2019.1708162
|View full text |Cite
|
Sign up to set email alerts
|

High risk of mumps infection in children who received one dose of mumps-containing vaccine: waning immunity to mumps in children aged 2-5 years from kindergartens in Jiangsu Province, China

Abstract: Background: During the period of immunization with a single-dose measles-mumps-rubella (MMR) vaccine, which has been available since 2008in China, the incidence of mumps in children aged 2-5 years has been high. The aim of this study was to determine the immunity profile of mumps in children aged 2-5 years as part of the assessment of the MMR vaccination strategy. Methods: A cross-sectional survey of IgG antibodies against mumps virus in children aged 2-5 years was performed. Analysis by enzyme-linked immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“… 19 , 21 Our research is consistent with these observations and likely provides an explanation of frequent mumps outbreaks in children and adolescents. 22 The mumps vaccine component of MMR elicits a lower immune response than do the measles and rubella components. 23 Studies in Scandinavia document persistence of antibodies in children derived from the Jeryl Lynn mumps strain, with 73% seroconversion in Sweden after a single dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 21 Our research is consistent with these observations and likely provides an explanation of frequent mumps outbreaks in children and adolescents. 22 The mumps vaccine component of MMR elicits a lower immune response than do the measles and rubella components. 23 Studies in Scandinavia document persistence of antibodies in children derived from the Jeryl Lynn mumps strain, with 73% seroconversion in Sweden after a single dose.…”
Section: Discussionmentioning
confidence: 99%
“…32 Sun and colleagues found that children who received a single dose of MMR vaccine in kindergarten, particularly 2-year-olds in northern Jiangsu province, China, were at high risk of mumps infection. 22 Mumps outbreaks occurred in campuses in Fujian Province in 2018, and the cases were mainly among 12–15 year olds. 10 , 11 Finally, MuV has only one serotype but 12 distinct genotypes (A – L).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted by Korczyńska and Rogalska, over 2000 cases of mumps were registered in 2014, and the majority of the sick children were not vaccinated or had only one dose of vaccine [15]. According to Sun et al, children vaccinated with only one dose of MMR vaccine were still at risk of viral infection in comparison to children immunised with the two doses of MMR vaccine [16]. Therefore, it is important to monitor childhood vaccination coverage and to educate parents on the necessity of receiving a second dose of MMR vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…There is other evidence supporting the meaningful importance of mumps intervention in the fight against mumps. First, since the program was introduced, children’s MMR vaccination rates have gradually increased year after year, with coverage rates for two year olds exceeding 95% in several provinces and cities of China [ 27 , 36 , 37 ]. Second, a study in Shanghai showed a high seroprevalence of mumps antibodies has been achieved in urban regions; mumps antibody seroprevalence reached 90% (95% CI: 90.0% to 90.2%) when adjusted for age and gender after the introduction of the MMR vaccination [ 27 ].…”
Section: Discussionmentioning
confidence: 99%